Organization Theory - Cunliffe, Ann L. (Los Angeles, California : Sage Publications, Incorporation, 2008)
This book provides a concise summary of the main topics, theories and issues in organization theory (OT). It also provides guidelines on how to make sense of course material, why it its important, and how to apply the theories and concepts to the design and management of organizations.